Frontolimbic Functioning During Threat-Related Attention: Relations to Early Behavioral Inhibition and Anxiety in Children - Fu, Xiaoxue (Biol Psychol, 2015)
Children with behavioral inhibition (BI), a temperament characterized by biologically-based hyper-vigilance to novelty, display threat-related attention biases (AB) that shape developmental trajectories of risk for anxiety. Here we explore the relations between BI, neural function, and anxiety. Fifty-six 9–12-year-olds (23 behaviorally inhibited) performed the dot-probe task while undergoing fMRI. AB scores were not associated with BI group or parent-rated anxiety symptoms. Trials requiring attention orienting away from threat engaged an executive and threat-attention network (dlPFC, vlPFC, mPFC, and amygdala). Within that network, behaviorally inhibited children showed greater activation in the right dlPFC. Heightened dlPFC activation related to increased anxiety, and BI levels accounted for the direct relation between dlPFC activation and anxiety. Behaviorally inhibited children may engage the executive attention system during threat-related processing as a compensatory mechanism. We provide preliminary evidence that the link between PFC functioning and anxiety might be attributed to early-emerging temperamental vulnerabilities present before the emergence of clinical anxiety.